SUSTAINABLE FINANCIAL PERFORMANCE BASED ON FINANCIAL LITERACY AND FINANCIAL INCLUTION WITH INNOVATION AS A MEDIATION VARIABLE ON BATIK MSMEs IN SRAGEN REGENCY - Edi Wibowo; Setyaningsih Sri Utami; Dewi Novita (International Journal of Social Science, 2022)
The purpose of this study is to analyze the significance effect of financial literacy and financial inclusion on innovation, analyze the significance effect of financial literacy, financial inclusion and innovation on financial performance and analyze the significance effect of financial literacy and financial inclusion on financial performance with innovation as a mediating variable. The population is the owner of Batik UMKM in Sragen Regency as many as 126 business actors with a sample of 56 respondents with simple random sampling. Data collection techniques used questionnaires. The data analysis technique used path analysis. The results showed that financial literacy and financial inclution has a significant effect on the innovation. Financial literacy, financial inclution and inovation have a significant effect on financial performance. Financial literacy and financial inclusion have a significant effect on financial performance with innovation as a mediating variable.